JURNALISTIK SEBAGAI METODE PEMBELAJARAN BAHASA ARAB - Farid Qomaruddin (MIYAH : Jurnal Studi Islam, 2022)
Abstract: Arabic, like other languages, has a systematic "learning in the classroom", but it becomes stagnant if it is not developed with critical thinking. Journalism is a scientific field that has many benefits when applied to the world of education. This study aims to contribute ideas in the field of Arabic language learning and Arabic learning methods, especially to the components in journalistic studies and journalism as a method of learning Arabic. This research uses a qualitative approach with the type of descriptive qualitative research with a Library Research study. Analysis of the data in this study used the Miles and Huberman model where in analyzing the data used data reduction, data display and conclusion drawing. The results of the study show that (1) journalism has complex components, wich it can be used in the process of learning Arabic both inside and outside the classroom. (2) Journalism can be called as an Arabic language learning method because it already has the requirements or criteria for a language learning method.‎